Enforcement of labor regulation and informality - Rita Almeida; Pedro Carneiro (Centre for Microdata Methods and Practice (cemmap), 2011)
Enforcement of labor regulations in the formal sector may drive workers to informality because they increase the costs of formal labor. But better compliance with mandated benefits makes it attractive to be a formal employee. We show that, in locations with frequent inspections workers pay for mandated benefits by receiving lower wages. Wage rigidity prevents downward adjustment at the bottom of the wage distribution. As a result, lower paid formal sector jobs become attractive to some informal workers, inducing them to want to move to the formal sector.
Keywords: 330; Arbeitsrecht; Rechtsdurchsetzung; Betriebsgröße; Arbeitslosigkeit; Brasilien